2018
DOI: 10.21608/edj.2018.77383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Root Canal Configuration of Permanent Mandibular Anterior Teeth in Egyptian Subpopulation: A Cone Beam Computed Tomography Study

Abstract: Cone beam computed tomography (CBCT) affords high-quality image with a relatively low radiation doses and low costs. It is considered as a valuable tool in endodontic field as it determines root morphology, number of roots, canals and accessory canals. The aim of the present study was to evaluate the permanent mandibular anterior teeth canal morphology in Egyptian subpopulation. Materials and Methods:A total of 100 patients were enrolled in this study and were assigned in two groups (50 females and 50 males). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…The present study showed that a type V Vertucci's classification was more common in men than women, with a statistically significant difference ( P =0.008). This result was in agreement with what was found by Basha in the Egyptian population [ 39 ]. On the other hand, Mashayakhy reported that in mandibular lateral incisors, there was no significant difference by gender among the different Vertucci canal classifications (type I, type III, and type V) [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
“…The present study showed that a type V Vertucci's classification was more common in men than women, with a statistically significant difference ( P =0.008). This result was in agreement with what was found by Basha in the Egyptian population [ 39 ]. On the other hand, Mashayakhy reported that in mandibular lateral incisors, there was no significant difference by gender among the different Vertucci canal classifications (type I, type III, and type V) [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
“…Studies on root canal anatomy of mandibular canine in Egyptian population is scarce, one study 43 examined a very small sample size (15 mandibular canines), even though they showed approximated percentage to our study for a second canal 33.3% with 13.3% for Vertucci type III, 13.3% IV and 6.7% V, this sample size cannot reflect a prevalence in a subpopulation. Another study 44 evaluated mandibular anterior teeth bilaterally in 100 patients with contradictory results to the present study as they concluded a 100% for Vertucci type I for mandibular canines with total absence of a second canal 44 , this could be attributed to the sample size which is one tenth of the current study sample size.…”
Section: Discussioncontrasting
confidence: 73%
“…14,15 Researchers have used a variety of methods and techniques to evaluate RMCC, including serial sectioning; 16,17 canal staining and clearing; 18,19 and radiographs, such as periapical or digital radiograph 5,19 and cone beam computed tomography. 2,3,[20][21][22][23][24][25][26][27][28] CBCT is a highly useful tool for noninvasive, 3D imaging. It is an accurate diagnostic tool for the effective diagnosis of RC morphology, including the length and number of roots and curvatures in sagittal and axial planes.…”
mentioning
confidence: 99%